Policy Recommendations on Accelerating Inclusive Employment of Persons with Disabilities in Bangladesh - World Bank (World Bank, Washington, DC, 2021)
Disability-inclusive development directly responds to the World Bank’s twin goals of ending extreme poverty and promoting shared prosperity. Disability and poverty are inherently linked, with persons with disabilities having poorer health outcomes; lower education achievements; less economic participation; and higher rates of poverty than people without disabilities. Poverty may also increase the risk of disability, by leading to the onset of health conditions associated with disabilities, such as malnutrition; low birth weight; lack of clean water and sanitation; and unsafe work and living conditions. The development challenges faced by persons with disabilities need to be addressed through a multisectoral and multidimensional approach that entails measures to improve accessibility and equality of opportunity; promotes participation and inclusion; and increases respect for the autonomy and dignity of persons with disabilities. Ensuring the social and economic inclusion of persons with disabilities in Bangladesh remains a challenge. To break the cycle of disability exclusion and poverty for persons with disabilities and their households, access to work and or livelihoods is essential. This note provides a set of recommendations to support the equitable participation and inclusion of women and men with disabilities in the labor market through a variety of mechanisms, including legislative policies; education and skills development; self and wage employment; social protection; accessibility; and the importance of changing attitudes.